Triassic lithostratigraphy of the Jameson Land Basin (central East Greenland), with emphasis on the new Fleming Fjord Group ... - Clemmensen, Lars; Kent, Dennis V.; Mau, Malte; Mateus, Octávio; Milàn, Jesper (Columbia University, 2020)
The lithostratigraphy of the Triassic deposits of the Jameson Land Basin in central East Greenland is revised. The new Scoresby Land Supergroup is now composed of the Wordie Creek, Pingo Dal, Gipsdalen and Fleming Fjord Groups. This paper only deals with the lithostratigraphy of the late Early-Late Triassic continental deposits of the latter three groups with emphasis on the vertebrate- bearing Fleming Fjord Group. The new Pingo Dal Group consists of three new formations, the Rødstaken, Paradigmabjerg and Klitdal Formations (all elevated from members), the new Gipsdalen Group consists of three new formations, the Kolledalen, Solfaldsdal (with the new Gråklint Member) and Kap Seaforth Formations (all elevated from members), and the new Fleming Fjord Group is subdivided into three new formations, the Edderfugledal, Malmros Klint and Ørsted Dal Formations (all elevated from members). The Edderfugledal Formation contains two cyclic bedded, lacustrine members, a lowermost Sporfjeld Member (elevated from beds), ...